Toward High-Performance Li Metal Anode via Difunctional Protecting Layer - Gu, Jinlei; Shen, Chao; Fang, Zhao; Yu, Juan; Zheng, Yong; Tian, Zhanyuan; Shao, Le; Li, Xin; Xie, Keyu (Frontiers in Chemistry, 2019)
Li-metal batteries are the preferred candidates for the next-generation energy storage, due to the lowest electrode potential and high capacity of Li anode. However, the dangerous Li dendrites and serious interface reaction hinder its practical application. In this work, we construct a difunctional protecting layer on the surface of the Li anode (the AgNO3-modified Li anode, AMLA) for Li-S batteries. This stable protecting layer can hinder the corrosion reaction with intermediate polysulfides (Li2Sx, 4≤x≤8) and suppress the Li dendrites by regulating Li metal nucleation and depositing Li under the layer uniformly. The AMLA can cycle more than 50 h at 5 mA cm-2 with the steady overpotential of lower than 0.2 V and show high capacity of 666.7 mAh g-1 even after 500 cycles at 0.8375 mA cm-2 in Li-S cell. This work makes great contribution to the protection of the Li anode and further promotes the practical application.